PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN, SISTEM ADMINISTRASI PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK PENGHASILAN DI KPP WILAYAH MALANG SELATAN (Studi Kasus Pada Kantor Pelayanan Pajak Pratama (KPP) Malang Selatan yang berada di Jl. Merdeka Utara No. 3, Kiduldalem, Kec. Klojen, Kota Malang Jawa Timur 65119) - Alifia Udlhiyana Shifa; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of taxpayer awareness, tax socialization, tax administration system, and tax sanctions on taxpayer compliance in paying income tax at KPP Pratama South Malang Region. The case study in this research is the Primary Tax Service Office (KPP) of South Malang which is located at Jl. Merdeka Utara No. 3, Kiduldalem, Kec. Klojen, Malang City, East Java 65119. The sampling method used purposive sampling. The data analysis method used multiple linear regression. samples that can be taken as many as 110 respondents. The results of the study are taxpayer awareness, tax socialization, tax administration systems, and tax sanctions simultaneously have a significant effect on taxpayer compliance in paying income tax. Taxpayer awareness partially has no effect on taxpayer compliance in paying income tax. Tax socialization partially has no effect on taxpayer compliance in paying income tax. The Tax Administration System partially has a positive effect on taxpayer compliance in paying income tax. Tax sanctions partially have a positive effect on taxpayer compliance in paying income tax. Keywords: Taxpayer Awareness, Tax Socialization, Tax Administration, Tax Sanctions, Taxpayer Compliance